OPTIONS SITUATIONAL EXERCISES IN THE TEXTBOOK OF UKRAINIAN LANGUAGE - Galaevskaya, Л. В. (Problems of the modern textbook, 2015)
The article raised the question of the use of case studies in modern textbook. Author determined functional characteristics and situational exercises the role in shaping the language communicatively competent person. The mechanismsof creation and practice of educational and speech situations as a means of implementing a communicative approach to teaching Ukrainian language; especially the use of situational exercises in the textbook on Ukrainian language.Formed characteristics situational exercises, in the light of the communication process modeling in communicative situations. Analyzed the relevance of communicative competence of students in today’s tutorial using situational exercises. Presented by classifi cation situational exercises. The concept «speech situation».